2016
DOI: 10.3928/01913913-20161027-01
|View full text |Cite
|
Sign up to set email alerts
|

Painful Acute Corneal Ulceration and Anterior Stromal Keratitis in an Adolescent With Reactive Arthritis

Abstract: Reactive arthritis is occasionally associated with conjunctivitis and uveitis, but rarely keratitis. The authors describe a patient with paracentral anterior stromal keratitis with overlying epithelial erosion and multiple satellite subepithelial infiltrates. The initial appearance and the severe pain were suggestive of an infectious process. Recovery was rapid following introduction of topical steroid, with features suggesting an immune process in the recovery phase. The authors suggest that a history of arth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…Lyons et al reported a patient with an atypical paracentral corneal ulcer with anterior stromal infiltrates mimicking microbial keratitis. 10 Our patient seems to closely resemble these cases. Microbiological evaluation revealed S. hominis in our patient, which is a commensal, though it is also known to cause infections.…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…Lyons et al reported a patient with an atypical paracentral corneal ulcer with anterior stromal infiltrates mimicking microbial keratitis. 10 Our patient seems to closely resemble these cases. Microbiological evaluation revealed S. hominis in our patient, which is a commensal, though it is also known to cause infections.…”
Section: Discussionsupporting
confidence: 74%
“…Lyons reported a similar approach in their case. 10 Our case was probably a mixed pathology of superadded infection with infl ammation due to ReA. Despite the epithelial healing, he was still symptomatic and had persistent pleomorphic anterior stromal infi ltrates.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations